Technology development for the preparation of quick - cooking fried rice and instant rice noodles - AMBILI V. KUMAR JUBY JOSE SOUMYA K. S; Dr. Ganesan V (Guide) (Tavanur 2003 Kelappaji College of Agricultural Engineering and Technology)
instant food basmati rice
Technology development for the preparation of quick - cooking fried rice and instant rice noodles